Pola Makan dan Status Gizi Sebagai Faktor Risiko Anemia Pada Remaja - Anggraini, Shelly Puspa; Fikha, Idri Iqra; Humairah, Anugerah; Febrina, Yori (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
Based on data from the World Health Organization (WHO) in world health statistics in 2021, it shows that the prevalence of anemia in women of reproductive age (15-49) ranges from 29.9%. The results of the Basic Health Research report (Riskesdas, 2018) show that the prevalence of anemia in adolescent girls ranges from 27.2% in the age group of 15-24 years. The purpose of this study is to determine the relationship between diet and nutritional status with hemoglobin levels in adolescent girls at the Babussalam Islamic boarding school in Pekanbaru. The method used in quantitative analytical research uses a crosssectional approach, where the research is carried out at the time of data collection between independent variables and dependent variables which are carried out together at the same time, with a large population of 78 adolescent female respondents in class XI and class XII of Babussalam High School Pekanbaru. Respondents were selected using the total sampling technique. The results of the statistical test showed that there was no significant average difference between diet and hemoglobin levels in the respondents because the p-value result was 0.4 >0.05. The results of the statistical test showed that there was no significant average difference between nutritional status and hemoglobin levels in respondents because the p-value result was 0.3>0.05. The conclusion was that there was no significant average difference between diet and nutritional status and hemoglobin levels in adolescent girls of Babussalam High School Pekanbaru